Efficient method for grand-canonical twist averaging in quantum Monte Carlo calculations - Azadi,S; Foulkes,WMC (Physical Review B: Condensed Matter and Materials Physics, 2019)
We introduce a simple but efficient method for grand-canonical twistaveraging in quantum Monte Carlo calculations. By evaluating the thermodynamic grand potential instead of the ground state total energy, we greatly reduce the sampling errors caused by twist-dependent fluctuations in the particle number. We apply this method to the electron gas and to metallic lithium, aluminum, and solid atomic hydrogen. We show that, even when using a small number of twists, grand-canonical twist averaging of the grand potential produces better estimates of ground state energies than the widely used canonical twist-averaging approach.